2020
DOI: 10.1111/nph.16398
|View full text |Cite
|
Sign up to set email alerts
|

Tenuazonic acid from Stemphylium loti inhibits the plant plasma membrane H+‐ATPase by a mechanism involving the C‐terminal regulatory domain

Abstract: Summary Pathogenic fungi often target the plant plasma membrane (PM) H+‐ATPase during infection. To identify pathogenic compounds targeting plant H+‐ATPases, we screened extracts from 10 Stemphylium species for their effect on H+‐ATPase activity. We identified Stemphylium loti extracts as potential H+‐ATPase inhibitors, and through chemical separation and analysis, tenuazonic acid (TeA) as a potent H+‐ATPase inhibitor. By assaying ATP hydrolysis and H+ pumping, we confirmed TeA as a H+‐ATPase inhibitor both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…TeA also overcame activation of the PM H + ‐ATPase by FC in a competition assay, suggesting that the C‐terminal regulatory domain is targeted by TeA. Further analysis indicated that TeA targets part of the C‐terminal regulatory domain of the PM H + ‐ATPase somewhere between the last 77 and 40 amino acid residues (Figure 5B), making the PM H + ‐ATPase able to bind fewer 14‐3‐3 proteins (Bjork et al, 2020).…”
Section: Microbial Derived Products That Directly Interact With H+‐at...mentioning
confidence: 99%
“…TeA also overcame activation of the PM H + ‐ATPase by FC in a competition assay, suggesting that the C‐terminal regulatory domain is targeted by TeA. Further analysis indicated that TeA targets part of the C‐terminal regulatory domain of the PM H + ‐ATPase somewhere between the last 77 and 40 amino acid residues (Figure 5B), making the PM H + ‐ATPase able to bind fewer 14‐3‐3 proteins (Bjork et al, 2020).…”
Section: Microbial Derived Products That Directly Interact With H+‐at...mentioning
confidence: 99%
“…TeA has several molecular targets in the cells of various organisms. In plant cells, it inhibits the proton pump of the plasma membrane and photosynthesis [ 80 , 81 ], being one of the pathogenicity factors of phytopathogenic fungi that produce it [ 82 ]. Cell-free assays demonstrated TeA to be an antioxidant and a promising inhibitor of acetylcholinesterase and β-amyloid aggregation [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, an increasing number of articles have reported its phytotoxicity. TeA showed an inhibitory activity against 4-hydroxyphenylpyruvate dioxygenase (HPPD) with an IC 50 of 18 µM [237] and plant plasma membrane (PM) H + -ATPase [238]. TeA was also able to inhibit the elongation of seedling roots and shoots [239][240][241], and resulted in a significant increase in multi-nucleolus of Vicia faba root tip cells at 400 µg•mL −1 [242].…”
Section: Tertramic Acidsmentioning
confidence: 99%